Peripheral Microangiopathy Changes in Pulmonary Arterial Hypertension Related to Systemic Sclerosis: Data From a Multicenter Observational Study - Giuggioli, Dilia; Riccieri, Valeria; Cipolletta, Edoardo; Del Papa, Nicoletta; Ingegnoli, Francesca; Spinella, Amelia; Pellegrino, Greta; Risa, Anna Maria; de Pinto, Marco; Papa, Silvia; Armentaro, Giuseppe; De Angelis, Rossella (Frontiers in Cardiovascular Medicine, 2022)
Systemic sclerosis (SSc) is a connective tissue disease characterized by immune-system alterations, fibrosis involving the skin and internal organs and diffuse microangiopathy. Pulmonary arterial hypertension (PAH) is a severe complication of SSc affecting about 10–15% of the patients and it is a leading cause of mortality. Due to the devastating nature of SSc-PAH, there is a clear need to systematically adopt appropriate screening programs. Nail fold videocapillaroscopy (NVC) studies have shown a more severe peripheral microvascular dysfunction in SSc patients with PAH suggesting that abnormalities in peripheral microcirculation may correlate with pulmonary microangiopathy. This is a cross-sectional study involving four tertiary University Rheumatology Units in the Center-North of Italy. Seventy patients, 35 adults with SSc and PAH confirmed by RHC (F/M 34/1; median age 65.2 ± 8.9 SD yrs), and 35 SSc patients without PAH were enrolled (F/M 3471; median age 63.3 ± 10.3 SD yrs). Clinical, laboratoristic and instrumental data were collected and NVC was performed in all patient. Specific NVC parameters were evaluated and a semi-quantitative rating scale was adopted to score these changes. Finally, patients were distributed into the suitable NVC pattern belonging to the scleroderma pattern. Our aim was to compare the peripheral microangiopathy changes in SSc patients with and without PAH, and to investigate the relationship between NVC findings and the main hemodynamic parameters of pulmonary vasculopathy. Patients with SSc-PAH+ showed a significant higher frequency of interstitial lung disease (ILD). No significant differences regarding clinical and laboratoristic parameters were observed. NVC abnormalities, avascular areas were more frequent in SSc patients with PAH, respect to those without (p = 0.03), and capillary density was significantly lower when considering grade 3 (p = 0.02). A higher NVC semiquantitative mean was found in SSc-PAH+ patients and a greater rate of the “late” pattern was detected in SSc-PAH+ subjects in respect to PAH- (57.1% vs. 25.7%) (p = 0.03). A significant correlations between pulmonary pressure values (sPAP by TTE and mPAP by RHC) and the capillary density (Spearman's rho 0.35, p = 0.04 for both). Our findings provide additional evidence to the literature data, confirming that a higher degree of peripheral nailfold microangiopathy is more common in SSc-PAH patients, and further strengthening the concept that NVC changes may run parallel with similar abnormalities inside pulmonary microcirculation.